Performance Evaluation of Virtualization Technologies for Databases in HPC Environments - Lange, Timoteo Alberto Peters; Cemim, Paolo; Rossi, Fábio Diniz; Xavier, Miguel Gomes; Belle, Rafael Lorenzo; Ferreto, Tiago Coelho; Rose, Cesar A. F. De (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD), 2012)
Modern database systems are applications that have a variable workload demanding a great share of the available resources during peak periods. To avoid sub utilization of resources during periods of low load, virtualization technology allows this type of application to be provisioned dynamically. This technique has improved in the last decades and new approaches are emerging to improve performance, like operating system level database virtualization. This paper analyzes the characteristics of this approach compared to traditional virtualization techniques.